Fluktuasi Populasi Wereng Coklat (Nilaparvata lugens Stal) di Kalitirto Yogyakarta Selama 10 Musim Padi - Kasumbogo Untung (Universitas Gadjah Mada, 1995)
Population observations of the brown planthopper and its predators were conducted at Kalitirto Agriculture Experimentation Station, Yogyakarta during 10 seasons from 1986/1987 Planting Season up to 1991/1992. Five rice varieties were planted under randomized completely block design consisted of one susceptible varieties (IR 36 and IR 64). No pesticides applied during the experimentation. The data showed that BPH populations were constantly low and under subeconomic condition. The BPH populations tend to decrease from first season to the following seasons. The populations of BPH were fully controlled by the population of predators complex. The total of predator populations always surpasses BPH population in every season. The ratio of predators and BPH’s population were increasing as planting seasons went along. The level of BPH resistance of rice varieties do not affect the fluctuation of BPH population and the total predators and BPH populations ratio.